Efficacy of plant products in controlling disease vector mosquitoes, a review - Hillary, V. Edwin; Ceasar, S. Antony; Ignacimuthu, S. (Entomologia experimentalis et applicata, 2024)
Mosquitoes pose a severe threat to the environment as vectors of numerous harmful diseases affecting humans and animals. Mosquitoes transmit pathogens that cause dengue, chikungunya, malaria, zika, yellow fever, Japanese encephalitis, and filariasis. Today's mosquito control strategies heavily rely on the use of chemical insecticides such as N,N‐diethyl‐meta‐toluamide (DEET), N,N‐diethyl mandelic acid amide (DEM), and dimethyl phthalate (DMP). However, the widespread use of chemical insecticides has resulted in pollution, bio‐magnification, and other health and environmental issues. It has also become ineffective because of the mosquitoes' aptitude to develop resistance, emphasizing the urgent need for safe, effective, and long‐lasting strategies. An alternative and promising approach to circumventing these obstacles involves the implementation of insecticides made from natural compounds found in plants. Therefore, the scientific community has shifted its focus towards plant‐based phytochemicals, oils, and extracts, as these are eco‐friendly, safe, and cost‐effective alternatives to conventional chemical insecticides. This review aims to provide details on current advances in plant‐based products (plant compounds, extracts, and essential oils), which are used to control all the life cycle stages (egg, larva, pupa, and adult) of the mosquito genera Aedes, Anopheles, and Culex. Hopefully, this review will pave the way to devise control strategies against these challenging pests. Mosquitoes (Diptera: Culicidae) are arthropod vectors involved in transmitting deadly infectious diseases to humans and animals, causing several million human deaths every year worldwide. Plant‐based products provide environment‐friendly mosquitocidal properties and are harmless to humans, non‐target organisms, and the environment. This review covers up‐to‐date information about plant products (plant compounds, extracts, and essential oils), which are utilized to control all the life cycle stages (egg, larva, pupa, and adult) of the mosquito genera Aedes, Anopheles, and Culex.